Detecção de coronavírus humanos em pacientes pediátricos com pneumonia atendidos em um hospital de referência em Fortaleza-Ce nos anos de 2011 e 2012 - Oliveira, Francisco Mário Sidney (2014)
Four genotypes of human coronavirus (CoVh-229E, OC43, NL63 and HKU1) are often associated with diseases of the upper respiratory tract as well as in the lower.Despite the diversity of human coronavirus associated with acute respiratory infections, little is known about the impact of infections associated with them in child populations living in tropical regions.The present study had as objective detect CoVh in nasopharyngeal samples from pediatric patients with pneumonia treated at emergency rooms and wards of a referral hospital in the city of Fortaleza - Ceará, during the years 2011 and 2012.To that end, we collected 522 nasopharyngeal aspirates, where the principle indirect immunofluorescence (IIF) was used for detection of influenza A and B viruses, respiratory syncytial virus, adenovirus and parainfluenza 1, 2 and 3, and 99 (19%) samples positive by this technique. Negative samples by IFA were subjected to polymerase chain reaction in real-time (RT-qPCR) for detection of CoVh. Of the 423 negative samples by IFA, 71 (16.80%) had a positive result for CoVh, where the type 229E was the most frequent (34.11%), followed by genotypes OC43 and NL63 with 28.23% each and with lower detection HKU1 genotype (9.4%).We observed 14 (19.71%) co-detections with at most two genotypes among CoVh.All types of CoVh were observed during the study period.A rate of 67.60% of the infected children was treated by CoVh in emergency, but it is worth mentioning the high detection rate in hospitalized patients (32.40%).HKU1 genotype identified in a child with one month old who died, where the only risk factor was age observed.Our results show the circulation four types of CoVh in our city,being detected in pediatric patients with pneumonia, demonstrating the potential importance of these viruses in severe respiratory syndromes.